Hybrids as potential mediators spreading non‐native genes: Comparison of survival, growth, and movement among native, introduced and their hybrid salmonids. Issue 2 (5th November 2019) - Fukui, Sho; Koizumi, Itsuro
Abstract: Comparing multiple fitness components and potential movement of wild hybrids with their parental species is necessary to fully understand the consequences of human‐mediated introgression, but studies tracking both parental species and their hybrids at the individual‐level are limited. Here, we compared growth, survival and movement of sympatric introduced brook trout (BT: Salvelinus fontinalis ) and native white‐spotted charr (WSC: S. leucomaenis ) with their hybrids (HYB) in a northern Japanese stream, using mark‐recapture data (1, 087 marked individuals) collected over 4 years (2013–2016). The mark‐recapture data with a single cohort showed that HYB had a comparable or even higher growth rate to BT and WSC. In addition, there is no evidence that hybrid survival was lower than both parental species throughout the entire study period. Furthermore, HYB showed high mobility equivalent to WSC, while BT showed the lowest mobility. Although our previous studies have documented the reduction of BT distribution and lowered reproductive success of HYB, non‐native genes can pose a threat to native WSC via relatively high survival, growth and/or mobility of HYB.